Promise Categories in Some American Drama Movies - Aida Minati Rohmah (Universitas Gadjah Mada, 2013)
This research attempts to investigate the promises in five American drama movies. The data comprise 73 promises collected from the subtitles of the movies Dear John, For Love of the Game, Going the Distance, Like Crazy, and The Notebook. Specifically, it aims to identify and categorize the promises, and to find out the more dominant type appears in those movies. The classification of the promises was according to Searle’s four felicity conditions: proportional condition, preparatory condition, sincerity condition, and essential condition. Based on the classification, it can be seen that all of the promises have fulfilled the four felicity conditions and the highest frequency of promises occurred in the movie Like Crazy (24.66%). The result also shows that 65 promises (89.04%) are categorized as implicit performatives and it appears as the more dominant type of promises in the data. The high number of implicit performatives indicates that the speakers might want to show their intention to do something in a casual way.